Ethnopedagogical Study of Local Wisdom Values as a Source of Learning for Forming Economic Behavior - Enceng Yana; Aan Anisah; Agung Yulianto (Journal of Innovation in Educational and Cultural Research, 2023)
This study aims to determine the values of Cirebon Batik's local wisdom that can be used as an alternative source and material for developing economic behavior. This research was designed qualitatively, collecting data through interviews, observation, and document analysis. The research was conducted in Cirebon Regency. The batik craftsmen were key informants, boutique owners, batik leaders, employees, and local government, who became supporting informants in this study. The results show three aspects of economic behavior in the activities of batik craftsmen: economic morality, rationality, and altruism. The value of local wisdom that can be used to determine student behavior is the attitude of morality reflected in the attitude of honesty, discipline, commitment, and prioritizing the interests of others. Rationality is reflected in the attitude of wisdom, feeling sufficient in economic terms, and effective and efficient consideration in economic aspects, and altruism is reflected in the attitude of concern for others, sincere sharing, and empathy. This study finds that traditional Cirebon batik motifs are relevant to the value of five characteristics of education, including religion, nationalism, independence, mutual cooperation, and integrity. The values in Cirebon batik motifs can then be used as a learning resource for students, especially for developing character education based on cultural heritage. The academic contribution of this research can improve good economic behavior in the midst of eroding moral values and the love of the younger generation for local culture. The results of this study can be used as a reference for stakeholders in instilling and developing positive character, wise and able to preserve the prevailing local wisdom values.